Social Determinants of Dementia Among Older Adults in Samarinda’s Urban Area - Oktaviani, Lisa Wahidatul; Ghozali, Ghozali; Rahman, Ferry Fadzlul; Ulan Ari, Maya Agustin (Preventia: The Indonesian Journal of Public Health, 2025)
Improving the quality of health and welfare of the population has an impact on increasing the number of lives in Indonesia. As a result, the number of elderly people and their proportions is increasing. Dementia is a condition where cognitive decline is so severe that it affects daily activities and social interactions. This condition of cognitive decline usually begins with a decrease in memory or memory abilities. Dementia that occurs among the elderly is caused by several factors, namely lifestyle, cognitive activities, family support, Activity Daily Living (ADL), self-esteem, quality of life, smoking behavior, knowledge, physical activity and sleep quality. Several previous studies have shown results relating to living in rural areas and dementia. This study aims to assess the correlation social determinant of Dementia Among Older Adults living in rural areas in Samarinda. This research uses a Cross Sectional research design, and Purposive Sampling is used as a sampling technique, with sample calculation using the Lameshow Formula and a sample size of 106 people is obtained which will be carried out in April until June 2024, apart from that it also uses the Spearman Rank Test for variables that use ordinal scale. The result shown that all of social determinants had strong correlation to dementia among older adults in Samarinda’s Urban Area. Lifestyle and cognitive activities have a very strong correlation with dementia among older adults. Providing motivation to increase self-esteem and adequate family support is a good prevention for the elderly in the urban area of Samarinda.